Efficacy of intravenous human immunoglobulin in renal transplant recipients with moderate to severe pneumonia - ZHU Bo-cheng; GE Guo-jun; REN Wen-li; LOU Bo-yang; ZHU Xiao-feng (Linchuang shenzangbing zazhi)
Objective To investigate the intravenous human immunoglobulin therapy in renal transplant recipients with moderate to severe pulmonary infection.Methods From October 2005 to July 2015,48 patients with moderate to severe pulmonary infection after renal transplantation in our department were analyzed.Twenty patients given daily intravenous human immunoglobulin(20 g for 3to 7 days)were taken as the treatment group,and the rest 23 patients without given intravenous human immunoglobulin served as the control group.The basic immunosuppressant was given in both two groups.The infection control time,fatality rate,length of hospital stay,and the occurrence of acute rejection and other indicators were observed in both two groups.Results The infection control time in the treatment group was significantly shorter than in the control group[(11.78±3.30)d vs.(15.13±3.30)d,P=0.004)].Twenty-three cases survived and2 died in the treatment group,and16 cases survived and 7 died in the control group with the difference being statistically significant(P=0.047).There was no significant difference in the length of hospital stay between the treatment group and the control group[(32.78±13.93)d vs.(30±23.87)d].There was no acute rejection in the treatment group,and 2 cases of acute rejection in the control group.Conclusions Intravenous human immunoglobulin can significantly reduce fatality rate of the renal transplant recipients with moderate to severe pulmonary infection and can significantly shorten the time of infection control.